Incidence of Bladder Cancer at a Tertiary Care Centre in North Karnataka - Shridevi Puranik; Shridhar Ghagane; Rajendra Nerli; Murigendra Hiremath (Middle East Journal of Cancer, 2022)
Background: Understanding the prevalence, clinical characteristics, and changing demographics of Indian bladder cancer (BC) has emerged as an important field of study. Herein, we aimed to present the case series of BC patients of a single tertiary care centre in North Karnataka.Method: This retrospective study was designed for 14 years from 2004 to 2017, conducted in the urology clinic. A total of 468 newly diagnosed BC patients (male = 415; female = 53) were included in the study. Sociodemographic, clinical characteristics, cystoscopic, and pathological findings were recorded and analyzed via IBM SPSS statistics software Inc. version 20.0.Results: The mean age of the patients was male = 62.27 years and female = 54.22 years. Hematuria was a common clinical symptom in both genders accounting for 42.02 versus 45.28% of the male and female subjects, respectively. Transition cell carcinoma (TCC) was the common variant seen in the male and female participants (92.99 versus 94.88%, respectively). Low-grade cancer was found in patients with >60 years of age in 39.7% versus 42.1% of respectively the males and females (P = 0.002) as compared to the patients <60 years. Non-muscle invasive BC in the males and females was respectively 55.42% versus 52.83%, whereas muscle-invasive cancer was 44.57% versus 47.16% respectively in the two groups (P = 0.008). 53 patients (29.22%) in the both genders received transurethral resection/intravesical Bacilli Calmette-Guerin therapy, which showed a significant improvement (P = 0.019). Conclusion: Transition cell carcinoma was found to remain the predominant type of BC with painless hematuria in North Karnataka population. This has seriously affected the public health; this trend is expected to be continued due to the high prevalence of smoking. There should be further emphasis on primary prevention of BC by conducting smoking cessation awareness programs.